Big data in agriculture and nutrition - Musker, Ruthie (International Food Policy Research Institute, 2019)
The food system community sees a huge potential for big data in agriculture to lift farmers out of poverty (Patel, 2013), and ensure that parents can feed their children nutritious, diverse foods (Lung’aho, 2018). In the USA, venture capitalists spent US$3 billion on ‘agtech’ (digital technology in agriculture) in 2016, with 46% of investors focusing on big data and analytics (Walker et al., 2016). Large data initiatives such as the CGIAR’s Big Data in Agriculture Platform have made thousands of datasets and publications available (Pineda, 2018). In order to establish a global data ecosystem that yields powerful insights and recommendations on the ways in which agriculture can improve nutrition, the community must ensure that the benefits of big data are for the betterment of all and not only for the few.